Effect of Soil Salinity and Sodicity on Seedling Growth and Mineral Composition of Pongamia pinnata - Singh, K.; Yadav, J. S. P. (Indian Forester, 1999)
Performance of Pongamia pinnata was evaluated under pot culture conditions at artificially created varying salinity (ECe) levels of 0.7, 4.2, 8.1, 16.3 and 32.5 dS m-1 and exchangeable sodium percentage (ESP) levels of 1.1,15.2,30.6,61.4 and 88.7 in an alluvial silty clay loam soil (Fine-loamy mixed hyperthermic Typic Ustochrept) by addition of different salts. Pongamia pinnata failed to grow at a level of ECe 32.5 dS m-1 and ESP at and above 30.6. Height, girth, fresh weight and dry weight of uprooted plants at the time of termination of experiment were found to have decreased with increase in ECe or ESP. Uptake of Na+ by plants increased progressively with increase in ECe or ESP levels, while the uptake of Ca++ decreased and Mg+ and K+ did not exhibit any definite relationship with increase in salinity or sodicity conditions. The values ofNaIK, Na/Ca and Na/Mg ratios in plants increased with increase in Ece or ESP. Relatively lower uptake of Ca++ due to high concentration of exchangeable Na+ appeared to increase the adverse effect of sodium on plant growth in saline and sodic soils.